Need of clinical services and training in fetal medicine in our Country - Íngar Pinedo, Hugo (2015)
Fetal medicine should be conceptualized as one that not only offers diagnosis and treatment for fetal pathologies but also prevents diseases and assures normality employing technology of universal use and demonstrated efficacy. Benefit of antenatal diagnosis in detection of serious fetal problems is no doubt clear. Correct management of each case with current knowledge will remarkably improve results in a wide range of fetal pathologies. It is necessary to make diffusion of this subspecialty so that people may have opportunity in improving fetal health. A change in health lineaments is needed incorporating national prenatal screening programs that will help diffusion and training of professionals for public health service and private practice.